Comparison of Production Levels and Rice Farming Income Using Technology And Corporate Farming (Case Study In Gapoktan Tani Mandiri Dalangan Village, Tawangsari District, Sukoharjo Regency, Central Java) - Ayuda Werti; Djoko Koestiono; Abdul Wahib Muhaimin (HABITAT, 2020)
This study aims to analyze the comparison of the level of production and income of rice farming using technology and corporate farming at Gapoktan Tani Mandiri in Dalangan Village, Tawangsari District, Sukoharjo Regency, Central Java. The analysis used is quantitative analysis which is used to analyze the comparison of the level of production and income of rice farming using technology and corporate farming. Based on the results of the study, there was a significant increase in production yield from before using corporate farming systems and systems (Second Planting Season 2014), which amounted to 6670 kg/ha after using technology and corporate farming systems (Second Planting Season 2018) of 8675 Kg/ha, which accompanied by a reduction in production costs by 13%. So there is a significant increase in income from before using corporate farming systems and technology (Second Planting Season 2014) of Rp. 17,546,541/ha after using corporate farming technology and systems (Second Planting Season 2018) reached Rp. 28,046,417/ha.